2007
DOI: 10.1007/s00428-007-0383-x
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A/STK-15 is a predictive factor for recurrent behaviour in non-invasive bladder carcinoma: a study of 128 cases of non-invasive neoplasms

Abstract: Aurora-A, a member of serine/threonine kinase, is implied in mitosis and centrosome maturation. Increasing levels of Aurora-A have been shown to be present in several malignancies and especially in bladder cancer. No immunohistochemical marker has shown to be able to predict the clinical outcome of patients with superficial bladder cancer, except MIB-1, as a predictive marker of relapse and progression. The aim was to investigate the expression of Aurora-A and MIB-1 in tissue micro arrays of superficial bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…In practice, this could mean that papillary urothelial neoplasms of low malignant potential and noninvasive papillary low-grade cancer with an absence of Aurora-A expression would require less frequent follow-up. The same study also demonstrated that the combination of Aurora-A and Ki-67 had a powerful predictive value for recurrence in multivariate analysis ( table 1 ) [83] .…”
Section: Aurora-a/stk15mentioning
confidence: 68%
See 1 more Smart Citation
“…In practice, this could mean that papillary urothelial neoplasms of low malignant potential and noninvasive papillary low-grade cancer with an absence of Aurora-A expression would require less frequent follow-up. The same study also demonstrated that the combination of Aurora-A and Ki-67 had a powerful predictive value for recurrence in multivariate analysis ( table 1 ) [83] .…”
Section: Aurora-a/stk15mentioning
confidence: 68%
“…In addition, Aurora-A overexpression may serve as an independent factor in predicting recurrence of pTa/pT1 tumors ( table 2 ) [82] . Similarly, immunostaining of Aurora-A in pTa tumors was demonstrated to be a good predictive factor for recurrence, especially in papillary urothelial neoplasms of low malignant potential and noninvasive papillary lowgrade cancer, while it was less useful in noninvasive papillary high-grade cancer and cancer in situ [83] . In practice, this could mean that papillary urothelial neoplasms of low malignant potential and noninvasive papillary low-grade cancer with an absence of Aurora-A expression would require less frequent follow-up.…”
Section: Aurora-a/stk15mentioning
confidence: 99%
“…p53 and MIB-1 usually display strong nuclear staining in Cis. Aurora-A is overexpressed in the cytoplasm and perinuclear in Cis, it has also been shown that overexpression of these 3 markers predicts relapse (30). One should also think of Cis extending to von Brunn Nests, or exclusively being present in the latter.…”
Section: Urothelial Carcinoma In Situ (Cis)/involvement Of Von Brunsmentioning
confidence: 99%
“…It is a known predictive factor of recurrence in UC and its overexpression has been shown to be a prognostic factor for bad clinical outcome [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of p53 gene and protein status provides information in assessing the clinical recurrence risk and progression in bladder cancer [3,4] .…”
Section: Introductionmentioning
confidence: 99%